Fractional active disturbance rejection control. (May 2016) - Li, Dazi; Ding, Pan; Gao, Zhiqiang
Abstract: A fractional active disturbance rejection control (FADRC) scheme is proposed to improve the performance of commensurate linear fractional order systems (FOS) and the robust analysis shows that the controller is also applicable to incommensurate linear FOS control. In FADRC, the traditional extended states observer (ESO) is generalized to a fractional order extended states observer (FESO) by using the fractional calculus, and the tracking differentiator plus nonlinear state error feedback are replaced by a fractional proportional-derivative controller. To simplify controller tuning, the linear bandwidth-parameterization method has been adopted. The impacts of the observer bandwidth ω o and controller bandwidth ω c on system performance are then analyzed. Finally, the FADRC stability and frequency-domain characteristics for linear single-input single-output FOS are analyzed. Simulation results by FADRC and ADRC on typical FOS are compared to demonstrate the superiority and effectiveness of the proposed scheme. Highlights: A fractional extended state observer is proposed for fractional order system. Fractional PD controller replaces TD plus nonlinear state error feedback in ADRC. Fractional order controller is applied in ADRC based on state estimations. Fractional active disturbance rejection control shows superior performance.